Formally verifying interactive systems : a review - Campos, J. Creissac (1997)
Although some progress has been made in the development of principles to guide the designers of interactive systems, ultimately the only proven method of checking how usable a particular system is must be based on experiment. However, it is also the case that changes that occur at this late stage are very expensive. The need for early design checking increases as software becomes more complex and is designed to serve volume international markets and also as interactions between operators and automation in safety-critical environments becomes more complex. This paper reviews progress in the area of formal verification of interactive systems and proposes a short agenda for further work.